Triaxial Tests on Granular Materials with Gradations without Oversized Particles and Reduced-Size Specimens - van Niekerk, A.A. (2025)
Modern research in pavement engineering is focused on determining the mechanical behavior of materials to serve as input data for mechanistic pavement design procedures. Regarding granular base materials, stress dependency in mechanical behavior (failure behavior, resilient behavior, and permanent deformation) is one of the most important aspects. Cyclic triaxial loading tests represent a reasonable method for simulating the stresses resulting from dead loads and traffic loads, and they can be performed on specimens that reflect the density, gradation, and moisture content properties present in the original pavement.